MANAJEMEN KONTEN INSTAGRAM MILIK PEMERINTAH DALAM PROMOSI POTENSI PARIWISATA DAERAH DI KABUPATEN BANYUMAS PROVINSI JAWA TENGAH - Shafira Anindyanari; Wisnu Widjanarko; Bambang Widodo (Jurnal Ilmu Komunikasi Acta Diurna, 2021)
Tourism is one of the many resources owned by Banyumas Recency, a small town located in Central Java Province, which has potential impact in increasing the independence and welfare of the community. To promote Banyumas tourism, a communication medium that is in tune with the present and can built public motivation and interest in visiting the location is urgently needed. Instagram is a social media that responds as a digital communication platform that has the ability to build a reputation and sustainable reciprocal relationships with audiences/publics. This research aims to identify how to manage the Instagram account content @dinporabudpar_banyumas in supporting the tourism potential promotion system in Banyumas Regency. Using a qualitative approach and content analysis, the data were obtained through the upload documentation in Instagram from 21 September until 31 December 2019. The results showed that the uploaded content was categorized into three types, namely cultural, natural and culinary tourism. Uploaded content combines photo and video aspects with attention to informative-persuasive text narrative. This capability in management will have an impact on the development of regional development and become a form of public relations articulation for the government that takes sides in the implementation of development. Keywords: Social Media, Instagram, Public Relations, Promotion, Tourism